In vitro Models of Breast Cancer Metastatic Dormancy - Montagner, Marco; Sahai, Erik (Frontiers in Cell and Developmental Biology, 2020)
Delayed relapses at distant sites are a common clinical observation for certain types of cancers after removal of primary tumour, such as breast and prostate cancer. This evidence has been explained by postulating a long period during which disseminated cancer cells survive in a foreign environment without developing into overt metastasis. Because of the inherent asymptomatic nature of this phenomenon, isolation and analysis of disseminated dormant cancer cells from clinically disease-free patients is ethically and technically highly problematic and, despite over the last decade protocols for purification and analysis of single cancer cells greatly improved, these data will likely be limited to the bone marrow. That said, detecting, profiling and treating indolent metastatic lesions before the onset of relapse is the imperative. To overcome this major limitation, in the last decade, many laboratories developed in vitro models of the metastatic niche for different organs and different types of cancers. In this review we focus specifically on in vitro models designed to study metastatic dormancy of breast cancer cells (BCCs). We provide an overview of the BCCs employed in the different organotypic systems and address the components of the metastatic microenvironment that have been shown to impact on the dormant phenotype: tissue architecture, stromal cells, biochemical environment, oxygen levels, cell density. A brief description of the organ-specific in vitro models for bone, liver and lung is provided. Finally, we discuss the strategies employed so far for the validation of the different systems and summarize.